Review of the Neotropical species of the genus Stereodermus Lacordaire, 1866 (Coleoptera: Brentidae, Stereodermini) - Mantilleri, Antoine; Sforzi, Alessandra (Zootaxa, 2006)
The genus Stereodermus is represented both in the Neotropical and Oriental regions. The 32 described neotropical species of the genus Stereodermus Lacordaire, 1866 are reviewed and an identification key and distributional maps are provided. Two new synonymies are proposed: Stereodermus longiceps Sharp, 1895 = S. pygmaeus (Gyllenhal, 1833), n. syn. and S. mitratus Sharp, 1895 = S. dentipennis Sharp, 1895, n. syn. All known species are redescribed and illustrated; six are new to science: S. attenuatus n. sp. (type locality: Peru, Iquitos), S. denisi n. sp. (type locality: Costa Rica, Provincia Puntarenas, Acosa, Estación Sirena), S. explanatus n. sp. (type locality: Costa Rica, Provincia Guanacaste, Volcan Cacao, Estacion Cacao), S. imparicostatus n. sp. (type locality: French Guyana, Roura Mountain, PK 41.1), S. paulettae n. sp. (type locality: Costa Rica, Provincia Puntarenas, Estación Sirena) and S. similis n. sp. (type locality: Brazil, Nova-Friburgo).